LA-Más : can co-leadership improve outcomes for organizations and the communities they serve? - Silver, Nora; Chung, Stella (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2021)
LA-Más is a nonprofit that combines design and architecture with policy experience to promote neighborhood resilience and elevate the voice of working-class communities of color in Northeast Los Angeles. The organization has created impactful projects from street improvements, enhanced storefronts, and affordable backyard homes (ADUs). Are co-leadership or gender the keys to its success? Some stakeholders said dual leadership-with its potential for additive skill sets and professional networks-enhanced an organizations' ability to authentically support diverse communities. Others said co-leadership brought more tensions and lack of clarity to an organization's mission. This case explores whether or not a co-leadership model would benefit an organization.
Orginally Published InSilver, N., & Chung, S. (2021). LA-Más: Can Co-Leadership Improve Outcomes for Organizations and the Communities they Serve?. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Leadership -- Case studies